2012
DOI: 10.1051/0004-6361/201014916
|View full text |Cite
|
Sign up to set email alerts
|

A mid-IR study of the circumstellar environment of Herbig Be stars

Abstract: Context. The study of the formation of massive stars is complicated because of the short times scales, large distances, and obscuring natal clouds. There are observational and theoretical indications that the circumstellar environment of Herbig Be (HBe) stars is substantially different from that of their lower mass counterparts, the T Tauri and Herbig Ae stars. Aims. We map the spatial distribution and mineralogy of the warm circumstellar dust of a sample of HBe stars. We compare our results to a sample of les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 56 publications
1
35
1
1
Order By: Relevance
“…V596 Car, Hen 3-331) is a Herbig Be star (B7-8Ve: Juhász et al 2010) located at 1.5 ± 0.5 kpc (Verhoeff et al 2012). The existence of a close binary companion interacting with the circumstellar disk of HD 85567 was proposed (Miroshnichenko et al 2001), and the binary companion with a separation of 0.…”
Section: A19 Hd 85567mentioning
confidence: 99%
See 2 more Smart Citations
“…V596 Car, Hen 3-331) is a Herbig Be star (B7-8Ve: Juhász et al 2010) located at 1.5 ± 0.5 kpc (Verhoeff et al 2012). The existence of a close binary companion interacting with the circumstellar disk of HD 85567 was proposed (Miroshnichenko et al 2001), and the binary companion with a separation of 0.…”
Section: A19 Hd 85567mentioning
confidence: 99%
“…To explain the observed IR emission, Acke et al (2008) adopted a geometric model consisting of three Gaussian disks, which can account for the IR emission but underestimates the observed submm/mm emission. Verhoeff et al (2012) have marginally resolved the PAH emission in the narrow-band peaking at 11.88 µm with VLT/VISIR, constraining a spatial extension of ∼ 110 AU in diameter. The mm observations obtained with the VLA and the IRAM Plateau de Bure interferometers (Alonso-Albi et al 2009) also showed that the MWC 297 disk is small, with an outer radius of ∼ 28 AU.…”
Section: A51 Mwc 297mentioning
confidence: 99%
See 1 more Smart Citation
“…The observing conditions were good for HD 169142 and HD 135344 in which the airmass was in between 1.0-1.1 and the optical seeing ∼0.6 and ∼0.8 respectively, and poor for HD 97048 in which the airmass was in between 1.6-1.7 and the optical seeing ∼1.3 . The spatial FWHM of the spectra and their PSF was extracted with the method described in Verhoeff et al (2012). VLT/VISIR data of Oph IRS 48 is taken from Geers et al (2007b).…”
Section: Q-band Imagingmentioning
confidence: 99%
“…First, we review a suggestion that HD 85567 might be a HAeBe star initially proposed by Thé et al (1994) and carried on in a number of later papers (e.g., Verhoeff et al 2012;Wheelwright et al 2013). This requires a comparison of the observed properties of HD 85567 with those of bona fide HAeBe stars.…”
Section: Single Starmentioning
confidence: 99%